Investigating the success of an E-Auction system initiatives among public servants: Validation of an integrated IS success model - Bandiyono, Agus; Muttaqin, Abdul Hamid Hudalil (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2020)
The implementation of an information system (IS) in public sector organizations was a crucial issue that needs to be addressed periodically. This study was conducted to examine the satisfaction factors of an E-Auction system adoption behavior by using the integrated IS Model of Delon, McLean, and Seddon. The usage of seven dimensions of the integrated IS model such as compatibility, the quality of a system, information, and service, perceived usefulness, and ease of use, to evaluate users satisfaction among public servants are still rare. This study was designed to focus on officials auctioneer that have experiences in using the E-Auction systems. The structured questionnaire with a five-point Likert scale and regression was chosen as the data collection and analysis method. This study found that there were only two of six variables (information quality and compatibility) that significantly prove as predictors of user satisfaction. Interestingly, our findings also found that there was no correlation between perceived ease of use and usefulness. Poor interface design, lack of technical support, and the usage of an E-Auction system that is classified as "order by mandate" were the primary concern that causes the insignificant relationship between variables. Therefore, to boost the satisfaction levels, further IS developers should pay more attention to improving information quality that is compatible with user needs.